Isolation of insecticidal lectinenriched extracts from African yam bean (Sphenostylis stenocarpa) and other legume species - Omitogun, O.; Jackai, L.E.N.; Thottappilly, G. (1999)
Insecticidal lectins were isolated from 20 resistant Vigna and non‐Vigna legumes and tested againstn 3 pests of cowpea namely: Maruca vitrata, Callosobruchus maculatus and Clavigralla tomentosicollis. Crude lectins were separated from seeds using sodium chloride extraction, ammonium sulfate fractionation, and dialysis. SDS‐PAGE indicated the molecular size of ca. 30 kDa for the most intense (and presumably active) band. Haemagglutination assays using trypsin‐treated rabbit erythrocytes suggested that lectins were among the extracted proteins. Extracts from Lablab purpureus and Sphenostylis stenocarpa both non‐Vigna spp., caused greater agglutination than those from the wild Vigna species. Bioassays on all three insect species using the lectin extracts incorporated in either artificial cowpea seeds (5% w/w) or in modified Vanderzant legume pod borer diet (1% w/v) indicated that the non‐Vigna extracts were highly toxic to the insects. Mortality after 10 days was >80% in the most toxic extracts. The extract from one of the accessions of Sphenostylis stenocarpa, an edible legume, was singled out for lectin purification and future gene cloning with the view of using it for engineering resistance to cowpea pests.